2010
DOI: 10.1095/biolreprod.110.084400
|View full text |Cite
|
Sign up to set email alerts
|

Cell Polarity Regulator PARD6B Is Essential for Trophectoderm Formation in the Preimplantation Mouse Embryo1

Abstract: In preimplantation mouse development, the first cell lineages to be established are the trophectoderm (TE) and inner cell mass. TE possesses epithelial features, including apical-basal cell polarity and intercellular junctions, which are crucial to generate a fluid-filled cavity in the blastocyst. Homologs of the partitioning defective (par) genes in Caenorhabditis elegans are critical regulators of cell polarity. However, their roles in regulating TE differentiation and blastocyst formation remain unclear. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 54 publications
12
125
0
1
Order By: Relevance
“…Trophectoderm-specific expression of Cdx2 is mediated by the establishment of apical cell polarity and position-dependent HIPPO signaling during the 8-cell to morula and morula to blastocyst transitions, respectively (Alarcon, 2010;Hirate et al, 2013). We previously showed that Pard6b is a direct target gene of TFAP2C in preimplantation embryos and TS-like cells (Choi et al, 2012).…”
Section: Tfap2c Regulates Apical Cell Polarity Via Pard6bmentioning
confidence: 99%
“…Trophectoderm-specific expression of Cdx2 is mediated by the establishment of apical cell polarity and position-dependent HIPPO signaling during the 8-cell to morula and morula to blastocyst transitions, respectively (Alarcon, 2010;Hirate et al, 2013). We previously showed that Pard6b is a direct target gene of TFAP2C in preimplantation embryos and TS-like cells (Choi et al, 2012).…”
Section: Tfap2c Regulates Apical Cell Polarity Via Pard6bmentioning
confidence: 99%
“…Recent studies show that developmental paucity of experimentally manipulated embryos can be "rescued" by culturing from the 8-cell stage in ESCM [31,76]. Such manipulations include the knockdown of Pard6b and Cdx2 genes by injection of RNA interference agents, which severely compromises embryo development in KSOM.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) RNA extraction from blastocysts, cDNA synthesis, and real-time PCR using the specific β-actin, Gapdh, Oct4 and Cdx2 primers were performed as previously described [31].…”
Section: Embryo Culturementioning
confidence: 99%
“…In the mouse embryo, Par3 and aPKC homologs regulate the orientation of cell cleavage planes as well as cell polarity and adhesion, which together can influence the allocation of blastomeres to an outer or inner position in the blastocyst. Par6 is essential for normal blastocyst formation in the mouse embryo [58]. Par6 gene knockdown resulted in cavitation failure without compromising blastomere cleavage or compaction by abnormal epithelial junctions, which then lead to defective paracellular permeability sealing in the outer cells of the embryo.…”
Section: Morulamentioning
confidence: 99%